Supplier Collaboration in ESG Implementation in the Automotive Industry in Purwakarta Regency - Na'afi, Septiana (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The implementation of Environmental, Social, and Governance (ESG) principles has become increasingly important in the automotive industry due to rising sustainability demands from regulators, global principals, and stakeholders. This study examines the role of supplier collaboration in supporting ESG implementation within the automotive industry in Purwakarta Regency, Indonesia, a region known for its growing manufacturing activities and integration into global supply chains. Using a qualitative research approach, data were collected through in-depth interviews with five informants representing automotive manufacturers and supplier companies. The analysis focuses on how collaborative practices shape ESG adoption at the operational level. The findings show that supplier collaboration is a key mechanism for translating ESG commitments into concrete practices, particularly through shared standards, joint audits, knowledge exchange, and capacity-building initiatives aimed at improving environmental performance and governance compliance. Long-term relationships and mutual trust were found to strengthen supplier engagement in environmental management, occupational safety, and ethical business practices. However, the study also identifies significant challenges, including uneven ESG awareness, financial constraints, and limited technical capacity among smaller suppliers, which can slow the pace of implementation. These challenges suggest that ESG adoption cannot rely solely on compliance-driven approaches but requires adaptive partnerships and continuous support from lead firms. This study contributes to the sustainable supply chain management literature by providing contextual insights from a regional automotive cluster in an emerging economy and offers practical implications for firms and policymakers seeking to enhance ESG performance through collaborative supplier engagement strategies.